PENERAPAN METODE EKSPERIMEN DALAM MENINGKATKAN PEMAHAMAN KONSEP IPAS SISWA DI SDN BUKIT MEDANG ARAK - Resty Restari Syahputri; Jelita; Nuraida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the implementation of the experimental method in improving fourth-grade students' conceptual understanding of Natural and Social Sciences (IPAS) on the topic of changes in the state of matter at SDN Bukit Medang Arak, to describe students' learning activities, and to describe the implementation of the experimental method during the learning process. This study used a descriptive qualitative approach through Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 21 fourth-grade students and one classroom teacher. Data were collected through observation, concept-understanding tests, interviews, and documentation, and analyzed descriptively using the Miles and Huberman model. The results showed an improvement in students' conceptual understanding from Cycle I to Cycle II. In Cycle I, the class average score was 74.00 with a completion rate of 71.43% (15 of 21 students). In Cycle II, the average score increased to 83.86 with a completion rate of 85.71% (18 of 21 students), an increase of 14.28 percentage points from Cycle I. Teacher implementation of the learning process was also categorized as good, reaching 83.3%. These findings indicate that the experimental method effectively improves students' conceptual understanding of changes in the state of matter by providing concrete and meaningful learning experiences